Compressive strength characteristic values of nine structural sized Malaysian tropical hardwoods - Azmi, Anis; Ahmad, Zakiah; Wei, Chen Lum; Baharin, Adnie; Za’ba, Nurul Izzatul Lydia; Mohamad Bhkari, Norshariza; Seng, Hua Lee (MDPI, 2022)
The design practice of timber structures in Malaysia is still based on permissible stress codes as stated in Malaysian Standard (MS) 544: Part 2 and MS 544: Part 3, which was adopted from the British Standard (BS) 5268. The British Standard was later completely replaced by Eurocode 5 (EC5) in 2009. Therefore, to preserve the continuity of design concepts specified in the British code of practice, local designers should adopt an EC5 limit state design to generate safe and economical designs. However, new strength data based on characteristic values which comply with EC5 for Malaysian tropical hardwoods are still lacking. The aim of this study was to investigate the compressive strength properties of nine structural-sized Malaysian tropical hardwood species namely Balau, Kempas, Kelat, Resak, Kapur, Keruing, Mengkulang, Light Red Meranti and Geronggang tested according to European Standard (EN) 408. A compression test was performed to measure the compressive strength and modulus of elasticity of the timbers and were used to derive characteristic values. The equation for determining characteristic compressive strength given in EN 384 was also assessed to verify that whether it is suitable for high density Malaysian hardwoods, as this equation was derived from softwood and European hardwoods. The results revealed that the derived characteristic values are higher than the values given in EN 338 for the relevant strength classes, particularly for heavy and medium hardwood with densities greater than 700 kg/m3. A verification of the equation used in EN 384 to determine compressive strength characteristic value yields a different equation, (Formula presented.). This shows that the EN 384 equation is not suitable to be used with hardwood timber with a density more than 700 kg/m3, since it will underestimate the strength value.